2022
DOI: 10.1037/xap0000393
|View full text |Cite
|
Sign up to set email alerts
|

Graphs do not lead people to infer causation from correlation.

Abstract: Media articles often communicate the latest scientific findings, and readers must evaluate the evidence and consider its potential implications. Prior work has found that the inclusion of graphs makes messages about scientific data more persuasive (Tal & Wansink, 2016). One explanation for this finding is that such visualizations evoke the notion of “science”; however, results are mixed. In the current investigation we extend this work by examining whether graphs lead people to erroneously infer causation from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…Some prior work has found that other types of data visualization, such as bar graphs (Tal & Wansink, 2016), increase the perceived credibility of data. However, more recent work has cast doubt on the validity of these findings (see Dragicevic & Jansen, 2017;Fansher et al, 2022). Future work could explore if including icon arrays influences the perceived trustworthiness of data.…”
Section: Discussionmentioning
confidence: 99%
“…Some prior work has found that other types of data visualization, such as bar graphs (Tal & Wansink, 2016), increase the perceived credibility of data. However, more recent work has cast doubt on the validity of these findings (see Dragicevic & Jansen, 2017;Fansher et al, 2022). Future work could explore if including icon arrays influences the perceived trustworthiness of data.…”
Section: Discussionmentioning
confidence: 99%
“…We extend the natural correspondence principles to examine how congruence between four displays and four decisions affects people's (a) comprehension, (b) confidence in their decisions, and (c) ratings of display helpfulness. Many studies have examined graph comprehension in terms of inferences drawn from main effects (Shah and Freedman, 2011) or the interpretation of causal and correlational relationships (Fansher et al, 2022). Here, we examine comprehension in terms of understanding uncertainties, as reflected in participants' interpretation, utilization, and evaluation of displays, in the message assembly and interrogation aspects of graph comprehension (Pinker, 1990).…”
mentioning
confidence: 99%